COLOUR ATTACHMENT IN BOBUR LYRICS (In the example of the work “Boburnoma”) - Ruziyeva , Sitora Asrorovna; Xasanova , Zarrina Shadiyarovna (Educational Research in Universal Sciences, 2023)
Zahiriddin Muhammad Bobur’s work “Baburname” is well-known throughout the world for its rare information. The classical work was translated into mor than thirty languages of the world and plays a significant role in the artistic relations of the country. The article analyzes the words and phraseological units related to colours used to express writers feelings of love and feelings of separation from the country and their translation into English. Lexical and semantic translations of phraseological units related to colours. The importance of translation and their methods in translations of classical work are discovered.